Perfil sociodemográfico e clínico de pessoas com urostomia em Belém, Pará, Brasil - PACHECO, Manuella da Silva (2019)
Introduction: A urostomy or urinary bypass consists of a surgically created opening in the abdominal wall for urine output involuntarily. Which demands the use of collecting equipment to collect the urine. Its purpose is the preservation of renal function, temporary or permanent, external or internal, continents or incontinent. Depending on the type of urostomy, there is a need for the use of collecting equipment and protective and safety adjuvants or urinary catheters after surgery. Objective: To describe the sociodemographic and clinical profile of people with urostomy. Descriptive, exploratory study, with a cross-sectional design and quantitative approach to the profile of people with stoma attended at a Nursing Consultation, in a Reference Service of Belém-PA, from 2014 to 2016. Methods: The data were collected together with the database of the research project Estomized Profile in the Amazon Context. As an exploratory analysis, descriptive methods were used to present data, worked and demonstrated in figures and tables. The Committee of Ethics and Research with Human Beings of the Federal University of Pará under the opinion No. 525.319 approved this study. Results: Among the 135 people with omen five men had urostomia, age group of 39 to 50 years, residing in the metropolitan region of Belém, had incomplete elementary education with monthly family income of up to one minimum wage. The primary cause of the urostomy was neoplasm. Definitive transiliary urostomy predominated in all cases. The mean time of use of the collecting equipment was 3 days, most reported being with altered skin peristomy. Conclusion: This study points out the need to include their results in planning health actions of the reference service in the city of Belém-PA.